Pengaruh Digital Marketing, Kepercayaan, dan Budaya Populer Terhadap Keputusan Pembelian Michuu Coffee - Regitha Cahyaputeri; Bruno Hami Pahar (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
The influence of globalization in Indonesia is felt and evidenced by the many foreign cultures that enter Indonesia, especially in Surabaya. More and more young entrepreneurs in Surabaya are working in the culinary field, especially foreign culinary. One of the foreign culinary businesses in Surabaya is Michuu Coffee Pakuwon City Surabaya which was established in 2019. Michuu coffee here offers South Korean food and beverage products that are in high demand these days. The purpose of this study is to know the impact of digital marketing, trust, and popular culture on decision purchases of michuu coffee. The population of this study is the consumer who make purchases at Michuu Coffee, where the number of samples is 75 respondents and the sampling technique is purposive sampling. On the validity test it is obtained results that all stated statement items are valid because r count > r tables (1.994) so that they can be used to help with this research. In the reliability test, all variables have Cronbach's Alpha results > 0.6 so that they are declared reliable. Then, in the classical assumption test with the normality test in this study, it is said to be normally distributed. In the multicollinearity test in this study, there was no multicollinearity. In the heteroscedasticity test in this study, there were no symptoms of heteroscedasticity. The multiple linear regression equation in this study is Y = -0.774 + 0.141 X1 + 0.503 X2 + 0.486 X3. In the coefficient of determination test in this study, having an adjusted R square value of 0.54 or 54% indicates that digital marketing, trust, and popular culture have a moderate contribution to purchasing decisions at Michuu Coffee. In the t-test, it was found that digital marketing variables (X1), trust (X2), and popular culture (X3) had a significant effect on purchasing decisions at Michuu Coffee.